STRATEGI PEMBELAJARAN BERBASIS PRAKTIK DALAM MENINGKAT-KAN KESIAPAN BERWIRAUSAHA MAHASISWA - Ziyadah El Fadllilah; Siti Anisa Al Maulani; Tia Meisaroh; Dwi Septi Rahayu; Ferida Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of practice-based learning strategies in enhancing students’ entrepreneurial readiness through a literature review approach. Practice-based learning is a learning method that positions students as active participants in the learning process through direct experiences, such as developing business plans, participating in business simulations, engaging in entrepreneurship projects, undertaking internships, and practicing product marketing. Theoretically, this approach is grounded in Kolb’s Experiential Learning Theory, which emphasizes that knowledge is acquired through the transformation of experience into meaningful learning. The findings indicate that practice-based learning contributes positively to the development of students’ entrepreneurial knowledge, skills, attitudes, and mindset. Through direct involvement in business activities, students are able to improve their communication, leadership, decision-making, problem-solving, creativity, and risk-taking abilities. Furthermore, the effectiveness of practice-based learning is influenced by internal factors, such as motivation, knowledge, and self-efficacy, as well as external factors, including family support, social environment, and institutional facilities provided by higher education institutions. The reviewed studies reveal that practice-based learning strategies are more effective than theory-oriented learning in fostering students’ entrepreneurial interest, readiness, and competencies. Therefore, higher education institutions need to optimize the implementation of practice-based learning through innovative and sustainable entrepreneurship programs to produce graduates who are not only prepared to seek employment but also capable of creating job opportunities.